Strategy for Hindi Text Summarization using Content Based Indexing Approach - Sargule, Swati; Ramesh M, Kagalkar (International Journal of Computer Sciences and Engineering, 2025)
The Document summarization provides summary of document in a very short time. Existing systems for document summarization have work carried on English text summarization. Such systems do not consider the context of the word to produce summary. Previously implemented document summarization models generally use the similarity among sentences in the original document to extract the most relevant sentences. The documents along with the sentences are generally indexed using standard term indexing computation methods, which do not take into account the context related to document. System takes Hindi document as input. That document undergoes through the algorithm and final output is produced as summary of input Hindi document by considering the context of the word. The Bernoulli Model of Randomness technique is used to check the probability of co-occurrences of two terms in large corpus. The methodology used contains lexical association, sentences indexing, word indexing.